Place Attachment and the Roots of Spiritual Relating in Animals - Brooks Pribac, Teya (Humanimalia, 2020)
This essay explores the possibility of place attachment (and aversion) as a relational framework through which animal bodies learn to communicate with intangible agencies within inhabited geographical spaces. I first briefly present my conceptualization of animal (human inclusive) spirituality along with relevant aspects of intersubjective attachment theory and self-formation. I then turn to place attachment.